Comportamento de cultivares de alface (Lactuca sativa L) na região serrana do estado do Rio de Janeiro - Rocha Leal , Nilton; Teixeira Liberal , Mozart; Gomes Coelho , Ronaldo (Revista Ceres, 2025)
Four lettuce cultivars were tested at the experimental station IPEACS at Avelar, Vassouras, Rio de Janeiro in spring- summer 1973. Yield results in kg/ha were as follows: ’Mesa 659’: 42,792; ’Forty-Niner’: 34,847;’Paris Island Cos’: 33,368 and ’Fulton’: 27,521. Although ’Mesa 659’ produced the highest mean weight per hectare, ’Forty-Niner’ yielded highest per individual Plant. ’Paris Island Cos’ was the earliest maturing variety, requiring 74 days to initiate seed stalk development.